Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Perilaku Konsumtif Pengguna Shopee Pay Later: Peran Moderasi Kontrol Diri pada Generasi Z - Avivi Hilwana. A; Umi Widyastuti; Diena Noviarini (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The advancement of technology-based financial services has significantly shaped consumer behavior, particularly among Generation Z. One such innovation gaining widespread use is the PayLater feature, which allows users to make purchases and defer payments to a later time. This study investigates the influence of financial literacy and lifestyle on the consumptive behavior of Shopee PayLater users, while also examining the moderating role of self-control. A quantitative research approach was employed by distributing online questionnaires to Generation Z individuals living in the Greater Jakarta area (Jabodetabek), targeting a sample size of 224 respondents. The data were analyzed using Structural Equation Modeling with a Partial Least Squares (SEM-PLS) approach. The results revealed that lifestyle has a positive and significant impact on consumptive behavior (t = 3.768; p = 0.000). Conversely, both financial literacy and self-control were found to have a negative and significant effect on consumptive behavior (t = 3.383 and 3.746; p = 0.001 and 0.000). Furthermore, self-control was shown to moderate the relationship by weakening the influence of both financial literacy and lifestyle on consumptive tendencies (t = 2.602 and 2.447; p = 0.009 and 0.014). All proposed hypotheses were supported by the findings, highlighting the critical role of enhancing financial literacy and strengthening self-control as key strategies to curb excessive spending behaviors among Generation Z. These insights are expected to serve as valuable input for PayLater service providers in developing more responsible and educational features tailored to the behavioral patterns of younger consumers.